International Migration, Economic Development and Policy - Özden, Çağlar; Schiff, Maurice (Washington, DC: World Bank and Palgrave Macmillan, 2012)
This volume reflects the expansion of the World Bank Research Program on International Migration and Development into new substantive and geographic areas. It presents a new global migration database and includes studies of the determinants and impact of return and circular migration, the impact of the flow of ideas on fertility, host country policies and their impact on immigrants, and the impact of international migration and remittances on poverty and other development indicators. The studies cover countries from Latin America, North Africa, South Asia, the South Pacific, and Western Europe, and show that the impact of migration on education and health tends to benefit girls more than boys, that its impact on labor force participation tends to be stronger for women than men, that return migrants tend to do better than non-migrants, and that fertility has tended to decline in countries whose migration has been to the West and has failed to do so in countries whose migration has been to the Gulf. The purpose of the case studies is to illustrate and clarify many theoretical mechanisms and to advance understanding of the impact of different migration policies, given that introducing policy variables in econometric regressions is generally difficult. Each study in this volume aims to answer a variety of development- and policy-related questions using the most appropriate of these three methodologies. These empirical studies and analyses include exploration of some novel hypotheses; they are also new in terms of the topics selected and the regions/ countries examined